Using outside readings to help students understand what economists do. Issue 4 (2nd October 2021) - Schneider, Patricia Higino
Abstract: How does one learn how to think like an economist without understanding what economists do? Using outside readings can be an effective and straightforward pedagogical tool to teach economic concepts and to expose students to the wide range of topics and methods economists use in their research. Improving students' understanding of what economists do is particularly important for increasing diversity in the field. The author of this article describes a formal approach to incorporate news articles in an introductory microeconomics course with two basic goals: to help students learn economics by applying economic concepts to the world they live in and to increase diversity in economics by exposing students to a broader set of topics studied by economists that better reflect their interests.